Pengaruh Isopropil Alkohol (IPA) pada Pembentukan Nanotitania Menggunakan Metode Hidrotermal pada Temperatur 250 oC - Maharani Maharani; Posman Manurung; Ediman Ginting (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
Research has been carried out on the effect of adding isopropyl alcohol (IPA) on the formation of nano titania. This study aims to determine the effect of adding IPA on the phase formation and particle size of TiO2. In this study, nano titania was synthesized by hydrothermal method at a temperature of 250oC with a variety of different IPA additions, namely 0.2 ml, 0.4 ml, 0.6 ml, and 0.8 ml. Samples were characterized using X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). The XRD characterization results showed that the diffraction peaks were following the standard database and showed anatase, rutile, and brookite phases. The particle size is calculated from the FWHM value using the Scherrer equation, which is in the 10-13 nm range for the anatase phase and the rutile phase in the 18-20 nm range. The results of SEM characterization in the 04IPA sample showed that the morphology was not perfectly round and the grain size was not uniform.